Prion disease and recommended procedures for flexible endoscope reprocessing – a review of policies worldwide and proposal for a simplified approach. Issue 1 (January 2020) - Kampf, G.; Jung, M.; Suchomel, M.; Saliou, P.; Griffiths, H.; Vos, M.C.
Summary: Several guidelines recommend specific treatments for endoscopes, procedures of quarantine for endoscopes, or additional treatments for the endoscope washer disinfector (EWD) in suspected or confirmed cases of Creutzfeldt–Jakob disease (CJD) or variant CJD (vCJD) but vary in many details. This study therefore reviewed guidelines on reprocessing flexible endoscopes after use in patients with suspected or confirmed prion disease. In addition, a literature search was performed in Medline on prion, CJD, vCJD, chemical inactivation, transmission healthcare, epidemiology healthcare, concentration tissue human and endoscope. Thus far, no case of CJD or vCJD transmitted by flexible endoscope has been reported. In animals it has been shown that oral uptake of 0.1–5 g of bovine spongiform encephalopathy (BSE)-infected brain homogenate is necessary for transmission. The maximum prion concentration in other tissues (e.g., terminal ileum) is at least 100-fold lower. Automated cleaning of endoscopes alone results in very low total residual protein ≤5.6 mg per duodenoscopes. Recommendations vary between countries, sometimes with additional cleaning, use of alkaline cleaners, no use of cleaners with fixative properties, use of disinfectants without fixative properties or single-use disinfectants. Sodium hydroxide (1 M) and sodium hypochlorite (10, 000 and 25, 000 mg/L) are very effective in preventing transmission via contaminated wires implanted into animal brains, but their relevance for endoscopes is questionable. Based on circumstantial evidence, it is proposed to consider validated reprocessing as appropriate in the case of delayed suspected prion disease when immediate bedside cleaning, routine use of alkaline cleaners, no fixative agents anywhere prior to disinfection and single use brushes and cleaning solutions can be assured.